Conspiracy theories and the COVID-19 pandemic in Japan : The rise, radicalization, and fall (?) of YamatoQ-kai - Demelius, Yoko; Szczepanska, Kamila (Oxford University Press, 2025)
This article investigates how conspiracy theories, spirituality, and resistance against pandemic-mitigation measures became intertwined during the coronavirus disease 2019 (COVID-19) crisis in Japan. Utilizing selected concepts from social movement theories (SMT), this case study-driven exploratory analysis focuses on the activities of YamatoQ-kai, a civil society organization that originated in a group of conspiracy-theory influencers and whose activities included the dissemination of an anti-immunization agenda. By analysing online posts on the organization’s homepage and journalistic reports on the organization, the article illuminates the underlying implications of the conspiracy theorists’ activism and demonstrates how the group adopted QAnon’s conspiracy rhetoric whilst taking a Japanized form. Second, it explains YamatoQ’s pivotal place amongst the Japanese societal actors espousing vaccine-hesitant attitudes. Finally, it shows how the group—as an unconventional case of conspirituality—created tangible experiences for followers and demonstrates the affective impact of group solidarity. In this way, the article’s findings contribute to closing the research gaps in scholarship on conspiracy theories, vaccine scepticism, and conspirituality.